Forgiveness and its Relationship with Depression - Muhammad Ali (Pakistan Journal of Positive Psychology, 2025)
The relationship between forgiveness and depression delves into the significant role of forgiveness in alleviating depressive symptoms. In this study a literature review spanning a decade of studies highlights the negative correlations between forgiveness and depression, establishing key propositions that suggest that unforgiveness is linked to poor mental health, while forgiveness acts as a beneficial coping strategy. The results reveal that engaging in forgiveness significantly diminishes depressive symptoms, enhances emotional well-being, strengthens interpersonal relationships, and lowers anxiety levels, contributing to an overall improved mental health. By emphasizing the transformative power of forgiveness, this research highlights its potential as a crucial therapeutic tool for enhancing resilience, emotional health, and ultimately leading to a more positive and fulfilling life experience.